CITRA KEPEMIMPINAN BUPATI KUANSING DI KECAMATAN INUMAN - Zariah Sonessa; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Regent is a very influential person in a district in building a region, it is this that determines the success or failure to develop an area. Performance and how to determine the success of regents leadership in his tenure. The success of the government (the regents) greatly affects to the image that he had, if the regent images is already not good it will affect to the growth and development of a particular area of the district. In his tenure, the Kuansing Regents doing some policies at the beginning of his reign. Kuansing Regents make policy to fired (layoffs) employees salary in the district Kuansing, this policy absolutely makes people feel very aggrieved. People consider that the regent was only concerned with his own interests and his group. This study aims to determine the leadership image of Regents in District Inuman, Kuansing and to determine the factors that affect to Kuansing Regents’s leadership image.This study used a qualitative descriptive method that based on primary data and secondary data source and use data collection techniques of observation, interview and documentation. The informants in this study are 14 people. Analysis technique using Miles and Huberman model of interactive data analysis, where the data obtained was then processed to be reduced, thus resulting presented a general conclusion, and data examination techniques using the extension of participation and triangulation, that used to compared between documentation data and the observation results.The results of this study indicate that the leadership image of Kuansing Regents in Inuman district was formed by stimuli, perception, cognition, attitudes, and by his own leadership style. In addition, the leadership image also formed by impressions, beliefs, and attitudes.Keywords: Imagery, leadership, Regent.